Glycoprotein VI Gene Variants Affect Pregnancy Loss in Patients With Platelet Hyperaggregability. (December 2018) - Sokol, Juraj; Skerenova, Maria; Biringer, Kamil; Simurda, Tomas; Kubisz, Peter; Stasko, Jan
The aim of our study was to evaluate GP6 gene in patients with sticky platelet syndrome (SPS) and fetal loss. Platelet aggregability was tested with platelet-rich plasma using PACKS-4 aggregometer (Helena Laboratories). High-resolution melting analysis on LightCycler 480 II (Roche Diagnostics) was used for single-nucleotide polymorphism (SNP) genotyping. We examined 64 patients with SPS and 54 control participants. We found significantly higher occurrence of 5 SNPs in patients with SPS versus controls (rs1671152, rs1654433, rs1613662, rs1654416, and rs2304167). Moreover, the haplotype analysis showed a significantly higher occurrence of 7 haplotypes in patients with SPS compared to controls (acgg and aagg in GP6_5reg haplotype; ccgt in GP6_3reg haplotype; gg and ta in GP6_REG haplotype; SKTH and PEAN in GP6_PEAN haplotype). Our results, especially higher occurrence of 4 nonsynonymous variants within the coding region, support the idea that GP6 polymorphisms are associated with the platelet hyperaggregability accompanied by fetal loss.